Tracking context‐specific transcription factors regulating hox activity. Issue 1 (26th July 2013) - Merabet, Samir; Dard, Amélie; Wellik, Deneen; Torres, Miguel; Ros, Marian
<x xml:space="preserve">Abstract</x> Background: Hox proteins are key developmental regulators involved in almost every embryonic tissue for specifying cell fates along longitudinal axes or during organ formation. It is thought that the panoply of Hox activities relies on interactions with tissue‐, stage‐, and/or cell‐specific transcription factors. High‐throughput approaches in yeast or cell culture systems have shown that Hox proteins bind to various types of nuclear and cytoplasmic components, illustrating their remarkable potential to influence many different cell regulatory processes. However, these approaches failed to identify a relevant number of context‐specific transcriptional partners, suggesting that these interactions are hard to uncover in non‐physiological conditions. Here we discuss this problematic. Results: In this review, we present intrinsic Hox molecular signatures that are probably involved in multiple (yet specific) interactions with transcriptional partners. We also recapitulate the current knowledge on Hox cofactors, highlighting the difficulty to tracking context‐specific cofactors through traditional large‐scale approaches. Conclusion: We propose experimental approaches that will allow a better characterisation of interaction networks underlying Hox contextual activities in the next future. Developmental Dynamics 243:16–23, 2014. © 2013 Wiley Periodicals, Inc.